Assessing the stregth and weldability of historic structural steel of historic structural steel = Ocena wytrzymałości i spawalności konstrukcyjnych stali historycznych - Dutkiewicz, Jacek; Gosowski, Bronisław; Organek, Piotr (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In practice, in the design stage of revitalization, renovation or reinforcement, there is often a need to determine the strength of steel as well as its weldability. The strength of steel can be determined in two ways: directly through destructive testing or indirectly - by the Brinell hardness test. In the case of weldability, this turns out to be much more difficult, because there are three groups of factors which determine this property, i.e.: local weldability, operative weldability, and overall weldability.
Keywords: wytrzymałość stali; twardość Brinella; spawalność; wskaźnik spawalności; próba spawalności; stal historyczna; strength of steel; Brinell hardness; weldability; weldability indicators; weldability testing; historical steel